A whole cell pathway screen reveals seven novel chemosensitizers to combat chloroquine resistant malaria - Ch'Ng, J; Mok, S; Bozdech, Z; Lear, M; Boudhar, A; Russell, B; Nosten, F; Tan, K (Springer Nature, 2013)
Due to the widespread prevalence of resistant parasites, chloroquine (CQ) was removed from front-line antimalarial chemotherapy in the 1990s despite its initial promise of disease eradication. Since then, resistance-conferring mutations have been identified in transporters such as the PfCRT, that allow for the efflux of CQ from its primary site of action, the parasite digestive vacuole. Chemosensitizing/chemoreversing compounds interfere with the function of these transporters thereby sensitizing parasites to CQ once again. However, compounds identified thus far have disappointing in vivo efficacy and screening for alternative candidates is required to revive this strategy. In this study, we propose a simple and direct means to rapidly screen for such compounds using a fluorescent-tagged CQ molecule. When this screen was applied to a small library, seven novel chemosensitizers (octoclothepin, methiothepin, metergoline, loperamide, chlorprothixene, L-703,606 and mibefradil) were quickly elucidated, including two which showed greater potency than the classical chemosensitizers verapamil and desipramine.